Keat Hwa High School Student Information System : Implementation and Evaluation - Liam, Choon Peng (2003)
Keat Hwa High School (KHHS) Student Information System (SIS) was designed, developed, and implemented primarily to assist the teachers, staff and school administrator to capture, to process and to manage the students’ data. The system was developed to function in compliance with the current software and hardware configuration within the school intranet environment. It was made up of a web based on-line student registration and an Open Database Connectivity (ODBC)-based system that provided academic and co-curriculum services. The structured methodology has been adopted to develop the system within the project schedule. The system was tested with the system users for user interface satisfaction, and perceived usefulness and ease of use. A set of questionnaire for User Interface Satisfaction basing upon classified variables such as reaction towards the developed software, the screen test and system capability was administered to two levels of academic students using the on-line registration. Students of both academic levels generally find the interface satisfactory. Another set of questionnaire was evaluated for perceived usefulness and ease of use by the school staffs. The system proved to be useful and easy to use to the staff. This study has provided an alternative of data collection and management for a small school and has also suggested further research to improve the system.